2013
DOI: 10.1364/ol.38.001906
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of terahertz spectra emitted from dual-frequency femtosecond pulse interaction in gases

Abstract: We demonstrate that the two basic physical mechanisms of terahertz (THz) generation in a femtosecond filament, namely, the free electron photocurrent and the nonlinear polarization of neutrals, can be identified through the spectral analysis of THz radiation. The contribution from the photocurrent peaks at the units of THz, while the neutrals yield the peak at the tens of THz. We suggest the practical implementation of such spectral analysis by varying the initial transform-limited laser pulse duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…The originally proposed model of THz pulse generation by four-wave mixing fails to explain all experimentally observed features of this process [6]. Later a model based on the transient photocurrent resulting from gas ionization was proposed, allowing * E-mail: pvch@inbox.ru ** E-mail: ushakov.aleksandr@physics.msu.ru *** E-mail: vladimir.bukin@gmail.com **** E-mail: rv_volkov@phys.msu.ru ***** E-mail: garnov@kapella.gpi.ru ****** E-mail: abst@physics.msu.ru agreement between the calculations and the experimentally obtained dependences [7,8]. Most experimental investigations into the features of the THz radiation generation mechanisms were carried out with linearly polarized radiation.…”
Section: Introductionmentioning
confidence: 92%
“…The originally proposed model of THz pulse generation by four-wave mixing fails to explain all experimentally observed features of this process [6]. Later a model based on the transient photocurrent resulting from gas ionization was proposed, allowing * E-mail: pvch@inbox.ru ** E-mail: ushakov.aleksandr@physics.msu.ru *** E-mail: vladimir.bukin@gmail.com **** E-mail: rv_volkov@phys.msu.ru ***** E-mail: garnov@kapella.gpi.ru ****** E-mail: abst@physics.msu.ru agreement between the calculations and the experimentally obtained dependences [7,8]. Most experimental investigations into the features of the THz radiation generation mechanisms were carried out with linearly polarized radiation.…”
Section: Introductionmentioning
confidence: 92%
“…First reported by Cook et al [3], THz emission from intense two-color pulses was initially attributed to optical rectification via third-order nonlinearity. However, it was shown later that the plasma builtup by tunneling photoionization is necessary to explain the high amplitudes of the THz field [4][5][6], and a quasidc plasma current generated by the temporally asymmetric two-color field is responsible for THz emission [7,8]. Plasma oscillations leading to strong THz radiation were also reported for single-color pump pulses with few-cycle duration or at higher intensities [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as an alternative approach, two-color laser field has been proposed to generate the intense and broadband THz pulse [14][15][16]. This intense THz generation created by the two-color laser field has attracted considerable attention in both its related application and physical mechanism [17][18][19][20][21][22][23][24][25][26]. This intense THz generation created by the two-color laser field has attracted considerable attention in both its related application and physical mechanism [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several experimental results confirmed that the THz intensity threshold was coincident with the ionization threshold of gas molecules, which indicated that the plasma formation plays an important role in the THz generation process [18,27]. Recently, a transient photocurrent model proposed by Kim et al was used to elucidate such THz generation in the two-color laser field [15,19], and has been studied in many experiments and theoretical simulations [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In this model, tunneling ionization and subsequent electron motion will form a directional current, which is responsible for the intense THz generation.…”
Section: Introductionmentioning
confidence: 99%